Risk factors of urinary incontinence among community dwelling older adults - Resshya Roobini Murukesu,; Devinder Kaur Ajit Singh,; Suzana Shahar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Urinary incontinence (UI) is a common disorder among older adults, with a global prevalence between 2% to 58%. UI has been associated with social isolation, increased morbidity and reduced quality of life (QoL). The aim of this study was to investigate the sociodemographic, clinical, cognitive and physical function risk factors of UI among Malaysian community dwelling older adults. This study is part of a larger scale population based longitudinal study on neuroprotective model for healthy longevity among older adults (LRGS TUA). A total of 1560 Malaysian community dwelling older adults aged 60 years and above were screened in this phase III LRGS study. Participants sociodemographic and clinical history were obtained. Mini Mental State Examination (MMSE), Rey Auditory Verbal Learning Test (RAVLT) and Digit Span tested cognitive function. Timed Up and Go Test (TUG), Hand Grip Strength Test, Chair Stand Test and Lawton Instrumental Activities of Daily Living tested physical function. The overall prevalence of UI was 15.7% (n = 245) in this study, with 11.8% (n = 88) in men and 19.3% (n = 157) in women. Logistic regression analysis showed that TUG (Adjusted odds ratio [OR], 1.071; 95% confidence interval [CI], 1.02-1.13), MMSE (OR, 0.93; CI, 0.90-0.97), weight (OR, 1.02; CI, 1.00-1.03), and constipation (OR 0.60; CI, 0.46-0.78) (p < 0.005) were significant risk factors of UI. The results indicate, decreased physical and cognitive function; increase in weight and having constipation increased the risk of UI. Maintaining optimum mobility, cognitive function, body weight and constipation prevention are vital in the prevention and management of UI among older adults.